Pääsuunnittelijan ja erityissuunnittelijan yhteisvastuu rakennussuunnittelussa - Lehtonen, Katja (Helsinki Law Review, 2013)
The purpose of the article is to first discuss the possibility of joint liability of the principal designer and the special designer towards the builder in a construction design project subject to the Land Use and Building Act (132/1999, amendment 222/2003 included). Secondly, attention will be given to the division of liability between the two designers, should the liability be considered joint. As the characteristics of construction projects vary significantly, the joint liability issues have in this article been presented on a general level only. Subject to the aforementioned Act, the builder appoints a principal designer that shall be in charge of the design in its entirety and design quality as well – this is done to ensure that the building design and any special designs form a complete entity which meets the requirements set for it. This “job description” of the principal designer has in the construction design field been perceived as rather wide-ranging. It may, as further discussed in this article, judicially be interpreted to even overlap the responsibilities of the special designer to some extent, thus providing for the possibility of joint liability. The final division of liability between the designers depends, however, mostly on factors that are determined on a case-by-case basis, and is thus difficult to generalize.